141 Switching from double-blind entacapone or placebo to open-label opicapone: NMSS results (1-year extension BIPARK-I study). Issue 12 (14th November 2019) - Fabregues, O; Tolosa, E; Ferreira, J; Lees, A; Santos, A; Rocha, J; Soares-Da-Silva, P
Abstract : Background: Opicapone (OPC), a novel once-daily peripheral COMT inhibitor, has shown to be safe and effective in reducing OFF-time in Parkinson's disease (PD) patients with motor fluctuations. Objective: To evaluate impact on non-motor symptoms in levodopa-treated PD patients who switched from placebo (PLC) or entacapone (ENT) to OPC in the BIPARK-I open-label extension (OLE). Methods: BIPARK-I, a multinational, multicentre, double-blind, 14–15-week, PLC and active-controlled study evaluated the efficacy of OPC 5 mg, 25 mg or 50 mg in PD patients with end-of-dose motor fluctuations. ENT was included as a reference arm. Following the double-blind BIPARK-I study, all eligible patients were switched to OPC 25 mg once-daily in a 1-year OLE regardless of prior double-blind treatment. After one week either OPC or levodopa could be adjusted according to response. This post-hoc analysis investigated impact on Non-Motor Symptoms Scale (NMSS) score in PLC and ENT 'switchers'. Results: Following the one-year OLE, NMSS changes (least-square mean [95%CI]) from DB baseline were -5.7, -4.7 and -2.0 and from OL baseline were -3.8, -0.2 and -0.4 for PLC, ENT and OPC 50 mg, respectively. Conclusion: No worsening NMSS score for subjects switching from double-blind ENT. PLC-switched subjects from DB to end of 1 year open-label OPC presented significantly less disability.